Hygienic Assessment of Students' Day Regime, Visiting Organizations Additional Education - Khazhimatov Ravshanbek Sobirzhanovich; Kosimov Sobirzhon Alisherovich (Scholars Digest Publishing, 2023)
Currently, the number of organizations is increasing to additional education, in which children have the opportunity to acquire new competencies. At the same time, classes in extracurricular organizations represent a separate component of students’ daily routine. [1] However, studies reflecting this aspect of lifestyle and its impact on the health of children and adolescents remain insufficient.